Behind the wheels with autism and ADHD: Brain networks involved in driving hazard detection. (February 2021) - Bednarz, Haley M.; Stavrinos, Despina; Svancara, Austin M.; Sherrod, Gabriela M.; Deshpande, Hrishikesh D.; Kana, Rajesh K.
Highlights: This study examined brain activation during driving hazard detection. Participants activated the social brain network when processing social hazards. Autism, ADHD, and typical development groups did not differ in brain activation. Driving experience predicted brain activation to social driving hazards. Abstract: Driving is a cognitively challenging task, and many individuals with autism spectrum disorder (ASD) or with attention-deficit/hyperactivity disorder (ADHD) struggle to drive safely and effectively. Previous evidence suggests that core neuropsychological deficits in executive functioning (EF) and theory of mind (ToM) may impact driving in ASD and ADHD. This functional magnetic resonance imaging (fMRI) study compares the brain mechanisms underlying ToM and EF during a hazard perception driving task. Forty-six licensed drivers (14 ASD, 17 ADHD, 15 typically developing (TD)), ages 16–27 years, viewed a driving scenario in the MRI scanner and were instructed to respond to driving hazards that were either "social" (contained a human component such as a pedestrian) or "nonsocial" (physical objects such as a barrel). All groups of participants recruited regions part of the "social brain" (anterior insula, angular gyrus, right middle occipital gyrus, right cuneus/precuneus, and right inferior frontal gyrus) when processing social hazards, and regions associated with motor planning and object recognition (postcentral gyrus, precentral gyrus, and supplementary motor area) when processing nonsocial hazards. While there were no group differences in brain activation during the driving task, years licensed was predictive of greater prefrontal and temporal activation to social hazards in all participants. Findings of the current study suggest that high-functioning ASD and ADHD licensed drivers may be utilizing similar cognitive resources as TD controls for decisions related to driving-related hazard detection.